Analisis Perlindungan Hukum terhadap Pelaku Usaha dan Konsumen Atas Penjualan Barang Oplosan - Farabi As-Sabili (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2024)
The rapid development of technology and industry has significantly impacted the trade sector. However, this progress also brings challenges, such as the phenomenon of adulterated goods sales by business actors. This phenomenon has detrimental effects on consumers and business actors who operate in good faith. This research aims to identify the forms of legal protection offered by Law No. 8 of 1999 concerning Consumer Protection for business actors and consumers in the context of adulterated goods sales. The research method used is normative legal research by examining literature or secondary data to find legal rules, principles, and doctrines. The findings indicate that legal protection can be achieved through dispute resolution both in court and out of court. Business actors and consumers can file criminal charges against business actors selling adulterated goods. In addition to criminal charges, consumers can also sue business actors selling adulterated goods through institutions responsible for resolving disputes between consumers and business actors.